Heat resistance of Rhizopus Sp. isolated from suman sa antala - Curameng, Sheryl Guillermo; Francisco, Ma. Leonora dL. (2004., 2004)
ABSTRACT Spoiled suman sa antala was subjeced to microbial examination to determine spoilage-causing fungi. The sample was allowed to spoil for one week at room temperature. Possible identities of the isolates were based on its macroscopic and microscopic characteristics: Aspergillus sp., Rhizopus sp., and Saccharomyces sp. The isolates were then exposed to different temperatures, 140°F, 149°F, and 158°F for 15 seconds to determine which of the three is the most heat resistant. At a temperature of 149°F, Rhizopus sp. was the only isolate that survived and was considered the most heat resistant isolate. Heat resistance characteristics of Rhizopus sp. were determined. D120°F was 66.14, D125°F was 17.42, D130°F 5.31 and D135°F was 1.36. An estimated z-value of 9°F was o
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Aspergillus; Snack foods -- Microbiology